Validity & reliability of OSCE/OSPE in assessing biochemistry laboratory skills of freshman nursing students of Shahid Beheshti University of Medical Sciences - Hosseini, saiedeh; Vartanoosian, jacqlin; Hosseini, fatemeh; Farzin Fard, farahnaz (Advances in Nursing & Midwifery, 2013)
Abstract Background and aim: Objective Structured Clinical/Practical Examination (OSCE/OSPE) is a well known evaluation method in medicaleducation. Lack of research in the evaluation of clinical/practical skills in basic sceinces was the justification for the present study to investigate the reliability and validity of OSCE/OSPE in the evaluation of biochemical lab skills of the first year nursing students. Materials and methods: This is an applied descriptive study. This study was carried out on 31 first year nursing students. At first the checklists were reviewd by the panel of experts, to implement their revisions and recommendations. According to research objectives 10 stations were designed. In each station two examiners separetely completed the checklists during a three days period (after 72 hours).The first day, the tests were given in 5 stations, the second day also in 5 other stations, and the third day the skills of the previous days were repeated in 10 stations.To check the content validity the checklists along with research objectives were given to 4 experts in the field. Criterion related validity, internal consistency, examiners reliability, and test- retest were checked. Findings: The findings showed a direct correlation between the total score gained in OSCE /OSPE and the scores from biochemical written test but it was not significant in terms of statistics, for the first observer calculated correlation was r =0.107, p=0.567 and for the second observer r =0.201, p=0.277. To find out the internal consistency, the correlation between the total score in OSCE/OSPE and the students’ average score in each station were examined. There was a significant correlation among total score and scores of nificant in 8 stations, but there was no significant correlation between the scores of two stations and the total score of the test in two other stations. A significant correlation between the results of the OSCE/OSPE by two examiners was obtained (r =0.859, p<0.001). In test re- test reliability, there was a significant correlation for the first examiner on the first and third day (r =0.681, p<0.001) also a significant correlation was found between the scores of the second examiner on the first and third day (r =0.671, p<0.001). In regards to Cronbach’s Alpha coefficent (= 0.907) the reliability of the designed research test was verified. Conclusion: Using the OSCE/OSPE as a valid and reliable method is recommended in assessing biochemistry laboratory skills. Keywords: OSCE/OSPE, Biochemistry Laboratory, Validity, Reliability